The Influence of Regional Own-Source Revenue and Balancing Funds on Capital Expenditure Allocation With Economic Growth as a Moderator (an Empirical Study of Regency/City Governments in Bali Province, 2019–2023) - Desak Gede Novita Anjani; Made Yenni Latrini (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Capital expenditure allocation refers to budget outlays for the acquisition of fixed assets and other long-lived assets, which play a crucial role in driving local economic activity. Key determinants include regional own-source revenue (PAD) and balancing funds (DAU, DAK, DBH), whose effects on capital spending may be moderated by economic growth. This study examines how PAD and balancing funds influence capital expenditure allocation across Bali’s nine regencies and one municipality from 2019 to 2023, and whether economic growth moderates those relationships. Using a sample of 45 yearly observations and moderated regression analysis, we find that both PAD and balancing funds exert significant negative effects on capital expenditure allocation. Moreover, economic growth does not significantly moderate these effects.